The Structural Complexity In Liszt's Transcription of Beethoven's 'Eroica' Symphony - Wu, Xiangyu; Djahwasi, Herry Rizal; Nasrifan, Mohd Nizam bin (Universitas Negeri Surabaya, 2025)
This study investigates Franz Liszt’s solo piano transcription of Beethoven's